1996
DOI: 10.1109/87.486344
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear control of synchronous servo drive

Abstract: The complete control design for a permanent magnet synchronous (PMAC) motor, derived from the input-output linearization, is presented in the paper. The motor model, written in the rotor's d-q coordinates, is nonlinear with respect to the state variables and linear in the control. The input-output linearization makes it possible to write the motor's model in Brunovski decoupled canonical form which makes the synthesis of linear controllers possible. The proposed control structure allows perfect tracking of smo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(17 citation statements)
references
References 8 publications
0
17
0
Order By: Relevance
“…The outputs y 1 and y 2 are called linearizing outputs or flat outputs [5], [9]. The input-to-flat output relation (44) is obtained with the help of the successive time derivatives of the components y i of the vector y such that in their relation with the control inputs u i , i = 1, 2, a well-defined vector relative degree [12] is established.…”
Section: Appendix B Input-state Linearizationmentioning
confidence: 99%
See 1 more Smart Citation
“…The outputs y 1 and y 2 are called linearizing outputs or flat outputs [5], [9]. The input-to-flat output relation (44) is obtained with the help of the successive time derivatives of the components y i of the vector y such that in their relation with the control inputs u i , i = 1, 2, a well-defined vector relative degree [12] is established.…”
Section: Appendix B Input-state Linearizationmentioning
confidence: 99%
“…With the stunning development of the semiconductor technologies, especially the digital signal processors (DSP), power electronics, and modern control techniques, more advanced control methods are being currently introduced to regulate the PMSM system, e.g., robust control [6], adaptive control [30], [31], sliding mode control [13], [27], input-output linearization control [9], flatness-based hierarchical control [5], adaptive backstepping control [23], [26], integrator backstepping control [24], and active disturbance rejection control (ADRC) [19], [28]. Generally speaking, these nonlinear control techniques improve the performance, robustness, and the stability of the PMSM system in closed loop.…”
mentioning
confidence: 99%
“…The nonlinear control based on the technique of linearization within the meaning of the input-outputs proved reliable on the level of the control of the asynchronous machine [2][3][4][5][6][7]. It was demonstrated that the nonlinear controller is adept nonlinearities and maintaining its performance in a wide operating range long and as long as the machine parameters are not changed.…”
Section: Introductionmentioning
confidence: 99%
“…In the last decade, nonlinear methods have become widely used also in the control of high performance AC servo-drives [l-31. In [4,5] we presented the control design based on elements of differential geometry providing exact linearization and decoupling with some robustness improvements obtained with Lyapunov min-max method and continuous variable structure control.…”
Section: Introductionmentioning
confidence: 99%